Dingoes can help conserve wildlife and our methods can tell. Issue 2 (27th January 2015) - Nimmo, Dale G.; Watson, Simon J.; Forsyth, David M.; Bradshaw, Corey J. A.; Frair, Jacqueline
Summary Management of apex predators is among the most controversial wildlife management issues globally. In Australia, some ecologists have advocated using the dingo, Canis dingo, as a tool for conservation management, due to evidence that they suppress invasive mesopredators. Hayward & Marlow (Journal of Applied Ecology, 51, 2014 and 835) questioned the capacity of dingoes to provide benefits to native biodiversity due to their inability to eradicate foxes and cats. They also argued that indices of abundance commonly used in studies of mesopredator release by dingoes (namely, track‐based indices) invalidate the conclusions of the studies. Hayward & Marlow caution conservation practitioners against incorporating dingoes into conservation programmes. Counter to their claims, we summarise research showing that the suppression of invasive mesopredators (cf. eradication) can enhance populations of native species and is therefore a meaningful conservation objective. We highlight literature supporting the hypothesis that dingoes suppress mesopredator abundance and activity, which in turn benefits native biodiversity. We show that Hayward & Marlow overlook many studies of carnivores that show track indices capture a large amount of the variation in the density of medium‐ and large‐sized carnivores. Synthesis and applications. Practitioners cannot afford to wait to act given the perilous state of Australia's mammal species, and we argue that the evidence is sufficiently strong to justify managing dingoes for biodiversity conservation.